Timing and dosage of and adherence to hormone replacement therapy and fracture risk in women with menopausal syndrome in Taiwan: A nested case-control study. (April 2021) - Chang, Cherry Yin-Yi; Tsai, Fuu-Jen; Chiou, Jian-Shiun; Chiu, Mu-Lin; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Liang, Wen-Miin; Lin, Ying-Ju
Highlights: Menopausal women had protection against fractures with higher dose of hormones. Menopausal women had protection against fractures with higher adherence to a hormone regimen. Progestogen showed a stronger protective effect than estrogen. Past exposure to estrogen or progestogen offered protection against fractures. Abstract: Objective: To investigate the association between hormone replacement therapy (HRT) and the risk of bone fracture in menopausal women in Taiwan. Study design: The longitudinal, population-based, nested case-control study in Taiwan involved 5269 women aged > 45 years with fractures and 21, 076 matched randomly selected controls without fractures. A conditional logistic regression model of analysis was employed. Main outcome measures: The association between the risk of bone fracture and various HRT-related parameters, including the timing, dosage, and adherence, was investigated. Results: Women with menopausal syndrome were protected from fractures when they received hormone drugs at high cumulative defined daily doses (DDDs) (Cumulative DDDs≥360) (odds ratio [OR]: 0.90, 95 % confidence interval [CI]: 0.82−0.99) and when their adherence was high (over 0.5) (OR: 0.70, 95 % CI: 0.60−0.82). The risk of fracture also decreased with high cumulative DDDs and high adherence combined (OR: 0.71, 95 % CI: 058−0.86). Subgroup analyses suggested that estrogen-containing regimens showed a protective effect against fractures at high cumulative DDDs or when adherence was high. Similar results were also observed with progestogen-containing regimens. Past exposure to an estrogen-containing regimen showed a protective effect against fractures when adherence was high. Past exposure to a progestogen-containing regimen showed a protective effect against fractures at high cumulative DDDs and when adherence was high. Conclusions: The results indicate that past exposure to estrogen-containing or progestogen-containing regimens exerts protective effects against bone fracture. These effects increased with higher cumulative DDDs and with adherence in a dose-dependent manner.